SHAPING E-COMMERCE PIONEERS: THE IMPACT OF FLIPPED CLASSROOM ON ’CROSS-BORDER E-COMMERCE OPERATIONS - Qiang, Li Wei (Top Educational Review Journal (TERJ), 2024)
The course "Cross-Border E-commerce Operations" in higher vocational colleges is designed to bolster students’ practical skills and employability. However, traditional teaching methods, characterized by one-way lectures, often result in passive learning and hinder educational outcomes. This paper addresses the imperative need to transition from passive to active learning. Students majoring in cross-border e-commerce typically exhibit a keen interest in emerging electronic products, new media, and social software. They are often outgoing and lively in nature, making them well-suited for the field. Nonetheless, several challenges hinder their professional development, including misconceptions about quick wealth in e-commerce and struggles with English language proficiency. Furthermore, inadequate computer skills and a lack of proactive learning are impediments to their progress. In response, this paper explores the implementation of the flipped classroom model, which blends teaching with real-world enterprise operations. This student-centered approach empowers learners to take the initiative in their education, transforming the learning experience into an engaging journey resembling a game. Moreover, the integration of 1+X certificates and skill competitions augments students’ sense of accomplishment in the classroom.